Efeitos de diferentes modalidades de exercício físico em indivíduos treinados sobre biomarcadores salivares e plasmáticos de estresse oxidativo e intensidade de exercício - Souza, Adriele Vieira de (2017)
The increase in antioxidant responses promoted by physical exercise is strongly associated with the attenuation of chronic oxidative stress and the improvement of cardiometabolic health induced by exercise. Thus, it is important to understand how distinct types of exercises can promote these biochemical alterations. In this study, 13 physically trained male subjects were submitted to 3 different acute physical exercise protocols: HIIE - High Intensity Interval Exercise, performed on a cycle ergometer, with 1 minute of exercise at 100% of VO2max followed by 1 minute of passive recovery at 40% of VO2max until voluntary exhaustion); EC - Continuous Exercise (performed on a cycle ergometer, consisting of a continuous exercise of 60 minutes with intensity between 50 and 60% of VO2max); ER - Resistance Exercise (3 sets of 12 maximum repetitions of resistance exercises of squat, leg press, flexor and stiff exercises). Blood and saliva samples were collected at the points: pre-exercise, post-exercise and 3 hours post-exercise. Biomarkers of oxidative stress (total antioxidant capacity, protein carbonylation, superoxide dismutase and catalase activities, levels of reduced glutathione and uric acid), markers of exercise intensity (salivary total protein and amylase activity) and salivary nitric oxide were evaluated. As a result, all exercise protocols showed increased protein concentration and salivary amylase activity at the post-exercise moment, indicating the similar and high load of the exercises, which is characterized by the intensity and volume ratio of the tests. An increase in nitric oxide levels was also observed, which was verified to be higher 3 hours after the protocols were performed. The antioxidant response profile of salivary samples was very similar to plasma, indicating saliva as an alternative tool in the study of oxidative stress in different exercise protocols. In general, antioxidant response was increased after exercise and it was found that a HIIE session exerts a similar pattern of antioxidant response compared to EC, while ER presented minor alterations. Thus, it is suggested that the favorable adaptations that occur in response to exercise-induced oxidative stress can be achieved relatively quickly through the practice of the high-intensity interval training.